Pre-clinical toxicity assessment of Artemisia absinthium extract-loaded polymeric nanoparticles associated with their oral administration - Kauser, Sana; Mughees, Mohd; Swami, Sanskriti; Wajid, Saima (Frontiers in Pharmacology, 2023)
Background: This study was designed to quantify the composition of ethanolic extract of Artemisia absinthium through GC-MS analysis and ensure in vivo safety of A. absinthium extract-loaded polymeric nanoparticles (ANPs) before considering their application as a drug carrier via the oral route.We synthesized N-isopropylacrylamide, N-vinyl pyrrolidone, and acrylic acid cross-linked polymeric NPs by free-radical polymerization reaction and characterized them by FTIR, transmission electron microscopy, and dynamic light scattering spectroscopy. Different concentrations of extract (50mg/kg, 300mg/kg and 2000mg/kg body weight) were encapsulated into hydrophobic core of polymeric micelles for assessment of acute oral toxicity and their LD50 cut-off value as per the test procedure of OECD guidelines 423. Orally administered female Wistar rats were observed for general appearance, behavioural changes and mortality for first 30 minutes, 4 hours, 24 hours and then daily once for 14 days.Result: ANPs at the dose of 300mg/kg body weight were used as an initial dose and rats showed few short-lived signs of toxicity, with few histological alterations in the kidney and intestine. Based on these observations, next set of rats were treated at a lower dose of 50mg/kg and a higher dose of 2000mg/kg ANPs. Rats administered with 50mg/kg ANPs remain normal throughout the study with insignificant histological disintegration, however, rats treated at 2000mg/kg ANPs showed some signs of toxicity followed by mortality among all three rats within 24-36 hours, affecting intestine, liver, and kidney. There were no significant differences in hematological and biochemical parameters among rats treated at 50mg/kg and 300mg/kg ANPs.We conclude that LD50 cut-off value of these ANPs will be 500mg/kg extract loaded in polymeric NPs.